2018
DOI: 10.1111/jcmm.14063
|View full text |Cite
|
Sign up to set email alerts
|

RNF168 facilitates proliferation and invasion of esophageal carcinoma, possibly via stabilizing STAT1

Abstract: Oesophageal cancer ranks as one of the most common malignancy in China and worldwide. Although genome‐wide association studies and molecular biology studies aim to elucidate the driver molecules in oesophageal cancer progression, the detailed mechanisms remain to be identified. Interestingly, RNF168 (RING finger protein 168) shows a high frequency of gene amplification in oesophageal cancer from TCGA database. Here, we report an important function for RNF168 protein in supporting oesophageal cancer growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
1
17
1
Order By: Relevance
“…34,35 Overexpression of STAT1 was observed in many SCCs and can promote the malignant ability of SCC. [36][37][38] Our findings suggested that TP63 and STAT1 may play a critical role in CSCC, and more studies on their mechanisms are necessary for the future.…”
Section: Discussionmentioning
confidence: 79%
“…34,35 Overexpression of STAT1 was observed in many SCCs and can promote the malignant ability of SCC. [36][37][38] Our findings suggested that TP63 and STAT1 may play a critical role in CSCC, and more studies on their mechanisms are necessary for the future.…”
Section: Discussionmentioning
confidence: 79%
“…To firmly confirm this effect, we further detected the effects of RNF168 on the expression of CSC markers and tumor‐initiating ability of NSCLC cells and a consistent result was obtained; however, further cytometry analysis should be performed to isolate CSCs in NSCLC cells, which might be a better model to investigate the effects of RNF168 on lung CSC progression. As an E3 ubiquitin ligase, RNF168 has been shown to facilitate proliferation and invasion of esophageal carcinoma, and drive breast cancer proliferation, by stabilizing STAT1 or promoting estrogen receptor ɑ transcription, respectively 9,22 . Notably, a recent study indicated that RNF168 could restrain gastric cancer progression by inducing ubiquitination‐proteasome‐mediating degradation of RhoC protein, 17 which is regarded as a fascinating CSC therapeutic target 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing insights into cancer biology, there are also records showing that RNF168 is elevated in the immunohistochemical results of human clinical tumor specimens, which may affect the response to standard treatment and some emerging cancer‐targeted treatments 8 . Recent studies have shown that RNF168‐mediated ubiquitin signaling suppresses the viability of BRCA1‐null breast cancer, 7 while RNF168 was shown to facilitate the proliferation and invasion of esophageal carcinoma 9 . However, it is still lack of in‐depth research of RNF168 in lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“… 32 The dysregulation of the JAK/STAT signaling pathway has been implicated in the initiation and progression of various cancers, including EC. 33 - 35 Yu et al found that the JAK-STAT pathway was significantly reduced by unbiased RNA sequencing in RNF168-depleted EC cell. Silence of RNF168 reduces JAK-STAT target genes, such as IRF1, IRF9, and IFITM1.…”
Section: Discussionmentioning
confidence: 99%